Fungal Infection in the Brain: What We Learned from Intravital Imaging - Shi, Meiqing; Mody, Christopher H. (Frontiers in Immunology, 2016)
Approximately 1.2 billion people suffer from fungal diseases worldwide. Arguably, the most serious manifestation occurs when pathogenic fungi infect the brain, often causing fatal meningoencephalitis. For most fungi, infection occurs via the vascular route. The organism must first be arrested in the brain microvasculature and transmigrate into the brain parenchyma across the blood-brain barrier. As a result, host immune cells are recruited into the brain to contain the fungi. However, it remains poorly understood how fungi traffic to and migrate into the brain and how immune cells interact with invading fungi in the brain. A new era of intravital fluorescence microscopy has begun to provide insights. We are able to employ this powerful approach to study dynamic interactions of disseminating fungi with brain endothelial cells as well as resident and recruited immune cells during the brain infection. In this review, with a focus on Cryptococcus neoformans, we will provide an overview of the application of intravital imaging in fungal infections in the brain, the recent findings revealed and possible future research directions using this powerful tool.